Legal Protection of Good Faith Buyers in Resolution of Land Rights Disputes - Rafael Tunggu (Eduvest - Journal of Universal Studies, 2024)
This research was carried out to determine and analyze legal protection for buyers in good faith in resolving land rights disputes. To achieve the research objectives, a document study has been carried out on the Decision of the Makassar District Court Number: 318/Pdt.G/BTH/2014, with three approaches, namely the conceptual approach, legislation and legal objectives. The research results show that in his legal considerations the judge stated that if the land sale and purchase transaction does not fulfill the "halal cause" element in accordance with the provisions of Article 1320 paragraph (4) of the Civil Code, then the buyer cannot be categorized as a buyer in good faith and therefore does not receive legal protection. The judge's consideration was seen as wrong because it did not take into account the element of the buyer's ignorance of the existence of hidden defects in the object of sale and purchase, that the object of sale and purchase was in the status of "dispute and court confiscation".